DIGITAL ECOSYSTEMS AS A NEW FORM OF EXISTENCE OF LARGE TECHNOLOGY COMPANIES AND COMMERCIAL BANKS - A. Khakirov; V. Akinina (Вестник Северо-Кавказского федерального университета, 2022)
The process of digital transformation of the economy has led to the accelerated development of innovative technologies that ensure the continuous operation of business processes of large technology companies whose activities are focused on the creation of these same technologies, and commercial banks that act as the main consumers of innovations in the IT sector. Over the past few years, Russian companies from these industries have embarked on the path of forming digital ecosystems to ensure the possibility of horizontal, vertical and conglomerate expansion of their activities in order to maximize financial results. Moving away from the concept of unidirectional activity is a byproduct of digital transformation, since the technologies used by companies allow creating uniied and interconnected economic systems within the organization and its partners, which leads to the emergence of a unique economic, digital ecosystem